The immortals of Meluha: book 1 of the Shiva trilogy - Amish (Shiva trilogy, 2010)
He has come -- Land of pure life -- She enters his life -- Abode of the gods -- Tribe of Brahma -- Vikarma, the carriers of bad fate -- Lord Ram's unfinished task -- Drink of the gods -- Love and its consequences -- The hooded figure returns -- Neelkanth unveiled -- Journey through Meluha -- Blessings of the impure -- Pandit of Mohan Jo Daro -- Trial by fire -- The sun & earth -- The battle of Koonj -- Sati and the fire arrow -- Love realised -- Attack on Mandar -- Preparation for war -- Empire of evil -- Dharmayudh, the holy war -- A stunning revelation -- Island of the individual -- The question of questions